The acute effects of fatiguing resistance exercise on mechanical power and force-time variables assessed during countermovement and squat jumping in elite female ski racers - Jordan, M. J.; Aagaard, P.; Herzog, W. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Elite alpine ski racing requires muscular strength and power, and causes neuromuscular fatigue (NF). NF has been identified as a factor in ACL injury, which greatly impacts ski racers. NF has central and peripheral mechanisms with the latter leading to prolonged force depression, which can persist for several days. The countermovement (CMJ) and squat (SJ) have been used to monitor NF, and may be useful for assessing acute and chronic NF for ACL injury-prevention. However, it is unclear which jump variables are suitable for this. The purpose was to assess change in mechanical muscle power and force-time variables during CMJ/SJ testing in response to fatiguing resistance exercise (F-RE) in elite female alpine ski racers (including World Cup medalists) over a typical off-snow training period in lead-in to the 2014 Olympic Winter Games.